ANALISIS PERAN TOKOH MASYARAKAT DALAM MEMPERTAHANKAN HARMONISASI KEHIDUPAN MASYARAKAT DI DESA BATU MAS - Elisabeth Noveliana; Yohanes Bahari; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This article is titled "Analysis of the Role of Community Leaders in Maintaining Harmonization of People's Lives in Batu Mas Village, Nanga Tayap District, Ketapang Regency". A common problem in this study is "How is the role of community leaders in maintaining the harmonization of people's lives in Batu Mas Village, Nanga Tayap District, Ketapang Regency?". The general purpose in this study is "To find out how the role of community leaders in maintaining the harmonization of people's lives in Batu Mas Village, Nanga Tayap Subdistrict, Ketapang Regency". The approach used in this study is qualitative approach with descriptive method. Data collection techniques used are observation techniques, interview guides, and documentation. The informants in this study are community leaders such as village heads, religious leaders, indigenous leaders, and educators in Batu Mas Village, Nanga Tayap Subdistrict, Ketapang Regency. The results of this study show that there is a role as a mobilizer, as a motivator and as an example of each community leader in an effort to maintain the harmonization of people's lives in Batu Mas Village.Keywords: Role of Community Leaders, Harmonization of Life, Society